2019
DOI: 10.1136/bjsports-2018-100486
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial decompression surgery for adults with shoulder pain: a systematic review with meta-analysis

Abstract: Objective To determine the benefits and harms of subacromial decompression surgery in adult patients with subacromial pain syndrome lasting for more than 3 months. Design Systematic review with meta-analysis. Main outcome measures Pain, physical function and health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 51 publications
2
65
0
10
Order By: Relevance
“…Parallel teams conducted these systematic reviews 1415. Another team updated a Cochrane systematic review synchronised with this BMJ Rapid Recommendation 16.…”
Section: Current Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Parallel teams conducted these systematic reviews 1415. Another team updated a Cochrane systematic review synchronised with this BMJ Rapid Recommendation 16.…”
Section: Current Practicementioning
confidence: 99%
“…This BMJ Rapid Recommendation is in response to two recent trials1213 which found that subacromial decompression surgery provided no benefit over placebo surgery. The recommendation is based on two linked systematic reviews on benefits and harms of subacromial decompression surgery and minimally important differences in patient reported outcome measures for shoulder pain, function and quality of life 1415. The main infographic provides an overview of the relative and absolute benefits and harms of surgery in standard GRADE format.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subacromial decompression with repair of teared tendons has been a very popular method to treat RCT for a long period of time, and the number of surgeries with subacromial decompression has increased signi cantly in the last two decades in America and the United Kingdom 3,4 . In most cases, the procedures of subacromial decompression consist of debridement of bursa, resection of anterior acromion and release of coracoacromial ligament without involvement of humeral head 5,6,7,8 . However, any impingement related with RCT is formed by both acromion and the GT of humerus, which means the GT is of equal important in the progression of subacromial impingement.…”
Section: Introductionmentioning
confidence: 99%
“…Styrken på anbefalingene er gradert etter kvaliteten på foreliggende kunnskapsgrunnlag/evidens vurdert med GRADE (Grading of Recommendations Assessment) (13,14), arbeidsgruppens råd og høringsuttalelser (ramme 2). I en artikkel i British Medical Journal fra 2019 basert på nye systematiske oversikter (15,16) anbefales ikke kirurgi ved subakromiale smerter (17). Vår veileder er publisert på Helsebiblioteket.no og gir konkrete anbefalinger ved subakromiale smerter og andre skulderdiagnoser (18).…”
unclassified